Mesonephric-Like Adenocarcinoma of Uterine Corpus: A Clinicopathological and Targeted Genomic Profiling Study in a Single Institution - Ma, Tianshi; Chai, Mengyu; Shou, Huafeng; Ru, Guoqing; Zhao, Ming (Frontiers in Oncology, 2022)
Background Mesonephric-like adenocarcinoma (MLA) is a recently characterized, rare, and aggressive neoplasm that mostly arises in the uterine corpus and ovary. MLA shows characteristic pathological features similar to mesonephric adenocarcinoma of the cervix. The origin of MLA is still controversial and recognition of it remains challenging for pathologists. The aim of this study was to enrich the clinicopathological features of MLA in the uterine corpus and explore its molecular alterations by targeted next-generation sequencing (NGS). Methods Four cases of MLA were identified among a total of 398 endometrial carcinomas diagnosed in our institution between January 2014 and December 2021. Immunohistochemistry and targeted NGS spanning 437 cancer-relevant genes were performed. Results The most common symptom was abnormal vaginal bleeding, and the average age was 68 years. Histologically, the tumors showed a mixture of varied growth patterns including papillary, glandular, tubular, cribriform, solid, and slit-like architectures, which were lined by columnar to cuboidal cells with overlapping vesicular nuclei and sometimes nuclear grooves. Intraluminal eosinophilic colloid-like secretions were focally evident in three of the four cases. Immunohistochemically, the MLAs were positive for GATA3 (4/4), TTF-1 (3/3), luminal CD10 (3/3), calretinin (2/3), and patchy P16 (3/3) and were negative for ER (0/4) and PR (0/4). The expression of P53 was “wild type” (4/4). By targeted NGS, 3/4 (75%), 2/4 (50%), and 1/4 (25%) cases harbored PIK3CA, KRAS, and PTEN mutations, respectively. None of the tumors had mutations in DNA mismatch repair genes, ARID1A/B, POLE, CTNNB1, SMARCA4, or TP53. At the time of diagnosis, three were presented with FIGO IB stage and one with IIIC stage. Two patients received postoperative chemotherapy and radiotherapy and they were alive without evidence of disease at 8 and 56 months follow-up, respectively. One patient developed pulmonary metastasis 13 months after surgery and chemotherapy, and one was dead of the disease 24 months after the operation without adjuvant therapy. Conclusions MLA is a rare and aggressive malignancy, representing approximately 1% of all endometrial carcinomas. It exhibits mixed architectures associated with distinctive immunophenotype and recurrent KRAS and PIK3CA mutations, supporting classified as of Müllerian origin with mesonephric differentiation.